Indigenous online cultural teaching and sharing : Kinship Project. - Mooney, Janet; Riley, Lynette; Howard-Wagner, Deirdre; Mooney, Janet; Riley, Lynette; Baker, Beverly; Kutay, Cat; Sim, Moira; Wain, Toni (Australian Department of Education and Training, 2017)
Report from the Kinship Project that developed an online teaching and learning tool incorporating narratives from Aboriginal community, Elders, students and staff into an online workshop for the purpose of cross-cultural learning. It was achieved through the development of online module. The module focuses on the different responsibilities assigned in Aboriginal society and the impact colonialism has had on Aboriginal people. The module was developed by translating an interactive face-to-face Kinship presentation to an online format, now called the 'Kinship Online Module'. The Kinship Online Module was developed in line with universities and the government's objective of enhancing learning and teaching in higher education. The project team achieved this by developing a framework for cultural competence training with high Aboriginal community involvement, which allows teachers to embed Aboriginal cultural learning and Aboriginal voices into mainstream courses of study. [p.13, ed]